EMPOWERMENT LEVEL AMONG RURAL WOMEN OF SINDH: A SOCIOLOGICAL ANALYSIS - M. Bukhari; G. M. Khushk; K. Khoso; S. Shah (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2024)
Women empowerment is an important factor in the growth of any country. It means equal social standing of women to their male counterparts in any society. However, even today, in the 21st century, women’s empowerment is a global issue and is prevalent in most societies, particularly in patriarchal societies. Since Pakistan is a patriarchal society, women in Pakistan are subjected to marginalization and social exclusion, especially in rural areas. This research work studied the complex nature of socio-economic factors and cultural norms that affect the empowerment level of rural women in Sindh, Pakistan, and what interventions can be implemented to improve their social, economic, psychological conditions, and political participation as well as decision-making power with an aim to achieve the following objectives: i) to study the socio-economic background of rural women; ii) to determine the social empowerment levels of rural women; iii) to determine the psychological empowerment; iv) to determine the economic empowerment levels; and v) to determine the political empowerment levels among the rural women of Sindh, province of Pakistan. The present study was conducted using a quantitative survey methodology with a close ended five-point Likert scale questionnaire focusing rural women of Sindh. The research questionnaire consisted of indicators related to socio-economic status, cultural norms, and empowerment level of rural women. The surveyed data was then analyzed using IBM SPSS software. Results drawn under the study inferred that the rural women of Sindh remain highly unempowered socially, psychologically, economically as well as politically with a weak socio-economic background. The study further recommends strong policymaking along with the introduction of various schemes in support of gender security by provincial and federal governments and strict measures taken for the implementation of policies.